The +299(G>A) resistin gene polymorphism and susceptibility to type 2 diabetes in Thais - Kanjana Suriyaprom (2018)
The prevalence of type 2 diabetes has been increased in Thais. Resistin is an adipokine that involve in glucose homeostasis and is a candidate gene for type 2 diabetes. We performed a case-control study in representative sample of 200 Thai volunteers, 105 controls and 95 type 2 diabetes subjects. The purposes of the present study were to investigate the association between two SNPs (single nucleotide polymorphisms) in the resistin gene, at positions +299(G>A) and -420(C>G), and biochemical parameters; to determine whether these polymorphisms are linked to increased risk of type 2 diabetes. At position +299(G>A) of the resistin gene, the resistin concentration among type 2 diabetes subjects was significantly higher in GA/AA genotypes (3.40 ng/ml) than the GG genotype (1.99 ng/ml). Resistin gene polymorphism at position +299(G>A) in type 2 diabetes patients was significantly more frequent than in the control group (p = 0.004). Polymorphism at position -420(C>G) showed no significant relationship with type 2 diabetes (p = 0.095). Logistic regression analysis was shown that +299(G>A) gene polymorphism was increased risk factors for type 2 diabetes (p = 0.013). In conclusion, these finding suggest that resistin gene polymorphism at position +299(G>A) has impact on the increased resistin concentrations and may influence susceptibility to type 2 diabetes in Thais.